Design of Circular Patch with Double C-Shaped Slot Microstrip Antenna for LTE 1800 MHz - Yusnita Rahayu; Jherino Permana Putra (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The design of a circular patch microstrip antenna with double C-shaped for LTE 1800 MHz is presented. The antenna is designed using FR-4 with dielectric constant of ε = 4.3, with thickness of substrate that is 1.6 mm and the thickness of patch and ground are 0.025 mm, Respectively the simulation results presented that the antenna works at frequency of 1714-1889.6 MHz, and work very well at frequency of 1800 MHz with a Return loss -20.484 dB, bandwidth 175.6 MHz. Technique used for broaden the bandwidth by using double C-shaped slot. In this paper presents S-Parameters, and Gain of microstrip antenna circular patch with double C-shaped slot.